Immigration and native labour market conditions in Argentina - González, Fernando Antonio Ignacio (2025)
This study examines the impact of immigration on the labour market conditions of natives in Argentina, a developing country with a long immigration tradition and high levels of informality. The outcomes of interest include labour income, unemployment rate and informality rate. The identification strategy employed is an instrumental variable estimation method that exploits the variability in immigrant settlement between Argentine regions. This strategy allows for estimating heterogeneous effects between different points in the income distribution of natives and does not require pre-assigning immigrants to skill groups. The results show that the arrival of immigrants does not worsen the labour market conditions of natives in terms of income, unemployment or informality. These results remain robust for multiple specifications and highlight the absence of negative effects on labour market conditions or on the subjective perception of such conditions. These results are critical for immigration policy development as they reveal that there is no scientific basis for restricting immigration flows based on concerns about the labour market conditions of natives.